Selective Antimicrobial and Antibiofilm Disrupting Properties of Functionalized Diamond Nanoparticles Against Escherichia coli and Staphylococcus aureus. (1st June 2015) - Khanal, Manakamana; Raks, Viktoria; Issa, Rahaf; Chernyshenko, Volodymyr; Barras, Alexandre; Garcia Fernandez, Jose M.; Mikhalovska, Lyuba I.; Turcheniuk, Volodymyr; Zaitsev, Vladimir; Boukherroub, Rabah; Siriwardena, Aloysius; Cooper, Ian R.; et al.
<x xml:space="preserve">Abstract</x> Diamond nanoparticles (NDs) have demonstrated great promise as useful materials in a variety of biomedical settings. In this paper, the antimicrobial and antibiofilm activities of variously functionalized NDs against two common bacterial targets Gram‐negative bacterium Escherichia coli and Gram‐positive bacterium Staphylococcus aureus are compared. Hydroxylated (ND‐OH), aminated (ND‐NH2), carboxylated (ND‐COOH), mannose (ND‐Mannose), tri‐thiomannoside (ND‐Man3), or tri‐thiolactoside (ND‐Lac3)‐modified NDs are fabricated and evaluated in the present work. Of these, the mannose‐modified NDs are found to interfere most strongly with the survival of S. aureus, but not to influence the growth of E. coli. In contrast, particles featuring lactosyl units have the opposite effect on S. aureus growth. Sugar‐functionalized NPs reported to display antibacterial effects are rare. Only ND‐COOH particles are seen to have any effect on the growth profile of E. coli, but the effects are moderate. On the other hand, both ND‐NH2 and ND‐COOH are found to inhibit E. coli‐induced biofilm formation at levels comparable to the known E. coli biofilm disruptor, ampicillin (albeit at concentrations of 100 μg mL−1). However, none of the modified particles examined here reveal any significant activity as disruptors of S. aureus‐induced biofilm formation even at the highest concentrations studied.